Accuracy of FIB-4 and APRI scores compared to transient elastography for liver fibrosis in patients with HIV and HBV co-infection. (January 2023) - Yang, Rongrong; Gui, Xien; Ke, Hengning; Yu, Xingxia; Yan, Yajun; Xiong, Yong
Background: Due to economic shortages and concern about occupational exposure to HIV, liver biopsy and transient elastography (TE) are rarely available in patients with HIV/HBV co-infection in China, where HIV/HBV co-infection is prevalent. Methods: The accuracy of FIB-4 and APRI for predicting liver fibrosis was compared with TE results in a series of 460 HIV/HBV co-infected patients. Results: FIB-4 and APRI scores were strongly correlated to liver stiffness measurement scores by TE, and the correlation index was 81.4–96.3. An FIB-4 index >1.5 had a positive predictive value of 95.2% to consider fibrosis with a sensitivity of 85.7%. An APRI index >0.5 had a positive predictive value of 98.2% to consider fibrosis with a sensitivity of 76.0%. A FIB-4 value <1.5 or APRI <0.5 were concordant with TE results to exclude fibrosis in 94.4% and 96.8%, respectively. A FIB-4 value >1.5 or APRI >0.5 were concordant with fibrosis diagnosed by TE in 77.6–89.4% and 70.7–80.9%, respectively. Conclusions: In areas with limited resources, FIB-4 and APRI indexes were accurate, simple and inexpensive methods for assessing liver fibrosis in patients with HIV/HBV co-infection.